2008
DOI: 10.1016/j.immuni.2008.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Effector Memory T Cells during a Delayed-Type Hypersensitivity Reaction and Suppression by Kv1.3 Channel Block

Abstract: SUMMARY Effector memory T (Tem) cells are essential mediators of autoimmune disease and delayed-type hypersensitivity (DTH), a convenient model for two-photon imaging of Tem cell participation in an inflammatory response. Shortly (3 hr) after entry into antigen-primed ear tissue, Tem cells stably attached to antigen-bearing antigen-presenting cells (APCs). After 24 hr, enlarged Tem cells were highly motile along collagen fibers and continued to migrate rapidly for 18 hr. Tem cells rely on voltage-gated Kv1.3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
256
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(276 citation statements)
references
References 48 publications
19
256
1
Order By: Relevance
“…Yet, our results seem to support this simple therapeutic hypothesis by showing that the observed reduction in infarct area and improvement in neurological deficit following PAP‐1 treatment is accompanied by a reduction in brain levels of IL‐1 β and IFN‐ γ , but not IL‐10 and BDNF or an impairment of phagocytosis. Another attractive feature of using Kv1.3 inhibitors to reduce neuroinflammation in the wake of ischemic stroke is that Kv1.3 inhibitors are known to be immunomodulators rather than immunosuppressants and do not impair the ability of rodents to clear acute infections or of primates to develop vaccine responses 5, 8. Kv1.3 inhibitors are therefore unlikely to further increase the risk of respiratory and urinary tract infections, which are responsible for considerable morbidity and mortality after stroke 45, 49.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, our results seem to support this simple therapeutic hypothesis by showing that the observed reduction in infarct area and improvement in neurological deficit following PAP‐1 treatment is accompanied by a reduction in brain levels of IL‐1 β and IFN‐ γ , but not IL‐10 and BDNF or an impairment of phagocytosis. Another attractive feature of using Kv1.3 inhibitors to reduce neuroinflammation in the wake of ischemic stroke is that Kv1.3 inhibitors are known to be immunomodulators rather than immunosuppressants and do not impair the ability of rodents to clear acute infections or of primates to develop vaccine responses 5, 8. Kv1.3 inhibitors are therefore unlikely to further increase the risk of respiratory and urinary tract infections, which are responsible for considerable morbidity and mortality after stroke 45, 49.…”
Section: Discussionmentioning
confidence: 99%
“…After the channel was cloned, the pharmaceutical industry initiated Kv1.3 discovery programs in the mid‐1990s but largely failed to identify compounds that were suitable for development 2. Interest in Kv1.3 afterward waned but revived following reports from our group that Kv1.3 is overexpressed in activated CCR7 − effector memory T‐cells (T EM ) and that Kv1.3 blockers therefore constitute immunomodulators rather than general immunosuppressants 3, 4, 5. Subsequent proof‐of‐concept animal studies demonstrated that the Kv1.3 blocking sea anemone Stichodactyla helianthus peptide ShK and its derivatives treat rat models of multiple sclerosis and rheumatoid arthritis,4, 5, 6 while our small molecule Kv1.3 blocker PAP‐1 prevents autoimmune diabetes4 in rats and treats psoriasis in a mouse xenograft model 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, mice fed an obesity-inducing diet rich in both fat and fructose (Tables S2 and S3) gain significant weight and adiposity, and develop insulin resistance within 6-8 wk (12)(13)(14)(15). As a Kv1.3 blocker we chose ShK-186 because of its picomolar potency (IC 50 69 pM), >100-fold selectivity over closely related channels, weak immunogenicity, and excellent safety profile in rodents and nonhuman primates (16)(17)(18)(19)(20)(21). Furthermore, ShK-186 is the first Kv1.3-specific blocker to advance to human safety trials as a potential therapeutic for autoimmune diseases.…”
mentioning
confidence: 99%
“…Imaging of inflamed tissues using confocal intravital microscopy has markedly improved our understanding of the actions of leukocytes at sites of inflammation (26)(27)(28)(29)(30)(31). However, extending this work to the examination of Treg function has been hampered by their scarcity and lack of a specific cell surface marker differentiating them from other CD4 + T cells.…”
mentioning
confidence: 99%